High LET-Like Radiation Tracks at the Distal Side of Accelerated Proton Bragg Peak - Horendeck, Dakota; Walsh, Kade D.; Hirakawa, Hirokazu; Fujimori, Akira; Kitamura, Hisashi; Kato, Takamitsu A. (Frontiers in Oncology, 2021)
Proton therapy is a type of hadron radiotherapy used for treating solid tumors. Unlike heavy charged elements, proton radiation is considered to be low LET (Linear Energy Transfer) radiation, like X-rays. However, the clinical SOBP (Spread Out Bragg Peak) proton radiation is considered to be higher in relative biological effectiveness (RBE) than both X-ray and their own entrance region. The RBE is estimated to be 1.1–1.2, which can be attributed to the higher LET at the SOBP region than at the entrance region. In order to clarify the nature of higher LET near the Bragg peak of proton radiation and its potential cytotoxic effects, we utilized a horizontal irradiation system with CHO cells. Additionally, we examined DNA repair mutants, analyzed cytotoxicity with colony formation, and assessed DNA damage and its repair with γ-H2AX foci assay in a high-resolution microscopic scale analysis along with the Bragg peak. Besides confirming that the most cytotoxic effects occurred at the Bragg peak, extended cytotoxicity was observed a few millimeters after the Bragg peak. γ-H2AX foci numbers reached a maximum at the Bragg peak and reduced dramatically after the Bragg peak. However, in the post-Bragg peak region, particle track-like structures were sporadically observed. This region contains foci that are more difficult to repair. The peak and post-Bragg peak regions contain rare high LET-like radiation tracks and can cause cellular lethality. This may have caused unwanted side effects and complexities of outputs for the proton therapy treatment.